Strategy For The Development of Palm Sugar Home Industry in Tolowe Ponrewaru Village Wolo District Kolaka Regency - Misnawati, Misnawati; Rianda, La; Indarsyih, Yusna; Surni, Surni (Jurusan Ilmu dan Teknologi Pangan, Fakultas Pertanian, 2023)
This study aims to determine the strategy of the developing a palm sugar home industry in Tolowe Village, Ponrewaru, Wolo District, Kolaka Regency. Determination of the location is done ( purposive ). Data was collected by using the methods of observation, interviews/questionnaires, documentation and literature review. The analytical method used is SWOT analysis. The results of the study of the value obtained from the IFE matrix (2.21) and the value obtained from the EFE matrix (2.18). The results of the alternative strategy using SWOT are S – O Strategy: Improving the quality and quantity of palm sugar products and developing marketing of palm sugar products. W – O Strategy: Conduct training for workers in the production process with community support and take advantage of the fluency of the industry to meet production needs. S – T Strategy: Establish good communication with the government and consumers and prepare a good production process to face competitors. W – T Strategy: Making appropriate financial policies and regulations for the development of the palm sugar industry and seeking market information about the price of palm sugar products.